Effects of Inspiratory Muscle Training and Early Mobilization on Weaning of Mechanical Ventilation: A Systematic Review and Network Meta-analysis - Salinee Worraphan (2020)
© 2020 American Congress of Rehabilitation Medicine Objective: To compare the effectiveness and rank order of physical therapy interventions, including conventional physical therapy (CPT), inspiratory muscle training (IMT), and early mobilization (EM) on mechanical ventilation (MV) duration and weaning duration. Data Sources: PubMed, The Cochrane Library, Scopus, and CINAHL complete electronic databases were searched through August 2019. Study Selection: Randomized controlled trials (RCTs) investigating the effect of IMT, EM, or CPT on MV duration and the weaning duration in patients with MV were included. Studies that were determined to meet the eligibility criteria by 2 independent authors were included. A total of 6498 relevant studies were identified in the search, and 18 RCTs (934 participants) were included in the final analysis. Data Extraction: Data were extracted independently by 2 authors and assessed the study quality by the Cochrane risk-of-bias tool. The primary outcomes were MV duration and weaning duration. Data Synthesis: Various interventions of physical therapy were identified in the eligible studies, including IMT, IMT+CPT, EM, EM+CPT, and CPT. The data analysis demonstrated that compared with CPT, IMT+CPT significantly reduced the weaning duration (mean difference; 95% confidence interval) (−2.60; −4.76 to −0.45) and EM significantly reduced the MV duration (−2.01; −3.81 to −0.22). IMT+CPT and EM had the highest effectiveness in reducing the weaning duration and MV duration, respectively. Conclusion: IMT or EM should be recommended for improving the weaning outcomes in mechanically ventilated patients. However, an interpretation with caution is required due to the heterogeneity.